Metabolite Transfer Between the Intestinal-Loop and the Gonadal Tissue in Pecten maximus (Molusca, Bivalvia) - Ita Widowati (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2001)
Problem of metabolite transfers from intestine to gonadal acini by way of macrophagous haemocytes was investigated in scallop Pecten maximus. A 1 ml of 4 mg/ml solution of Cadmium-free ferritin (Sigma) was injected into the lumen of the proximal extremity of descending portion of the intestine. Two types of experiments were carried out, in vivo and in vitro. For the first, observation by light and electron microscopy was showed that ferritin was detected in the lumen and between the microvilli. In the intestinal cells, ferritin was observed in the vacuoles and lysosomal type. Under basement lamina, it is noted the presence of ferritin on underlying connective tissue, macrophagous haemocytes and near the gonadal acini male and female. The in vitro experiments gave the same results. Based on these results. it is concluded that intestine play a role in the nutrition for gametogenesis and that the metabolite transfer is by way of macrophagous haemocytes.